Attentional Considerations in Advanced Air Mobility Operations: Control, Manage, or Assist?. (September 2022) - Sato, Tetsuya; Politowicz, Michael S.; Islam, Samia; Chancey, Eric T.; Yamani, Yusuke
The implementation of automation will enable Advanced Air Mobility (AAM), which could alter the human's responsibilities from those of an active controller to a passive monitor of vehicles. Mature AAM operations will likely rely on both experienced and novice operators to supervise multiple aircraft. As AAM constitutes a complex and increasingly autonomous system, the human operator's set of responsibilities will transition from those of a controller, to a manager, and eventually to an assistant to highly automated systems. The development of AAM will require system designers to characterize these three sets of human responsibilities. The present work proposes different human responsibilities across various roles (i.e., pilot in command, system operator, system assistant) in the context of AAM along with pertinent attention-related constructs that could contribute to each of the three identified roles of AAM operators including situation awareness, workload, complacency, and vigilance.